Artificial Intelligence as a Geopolitical Asset: China’s Strategy and Its Global Impact - Mestre Gascón, Antoni; García Rodríguez, Javier (Journal of the Spanish Institute for Strategic Studies, 2025)
Artificial Intelligence (AI) has become a key factor in 21st-century geopolitical competition, with China emerging as a dominant player in its development and application in security and defense. Through initiatives such as DeepSeek and its ambitious national AI plan for 2030, China aims to establish itself as a global leader in this technology, generating significant strategic implications for international security. This article examines the impact of Chinese AI in three dimensions: its role in cybersecurity and hybrid warfare, the development of autonomous systems and their use in defense, and the regulatory and strategic challenges posed by its global advancement. It analyzes the responses of major powers such as the United States and the European Union, the role of AI in deterrence and hybrid conflicts, and the need for international regulatory frameworks to mitigate the risks associated with its proliferation. Drawing on an analysis of recent sources and strategic studies, this paper argues that Chinese AI not only redefines the global balance of power but also presents critical challenges in terms of security, technological governance, and international stability.
Keywords: artificial intelligence; Geopolitics; Defece Technology; China